Synthesis of Functional Carbo-benzenes with Functional Properties: The C2 Tether Key - Cocq, Kévin; Barthes, Cécile; Rives, Arnaud; Maraval, Valérie; Chauvin, Remi (Synlett, 2019)
Beyond demonstration of conceptual relevance and synthetic feasibility of aryl/alkyl-substituted representatives, carbo-benzene molecules started to gain prospects of broader impact through the emergence of alkynyl derivatives. This is first illustrated by examples of di- and hexaalkynyl-carbo-benzenes, a carbo-naphthalene, a carbo-biphenyl, and two carbo-terphenyls. A focus is then given to dialkynyl derivatives by reference to the peripherally C2-extruded parents. In the centrosymmetric quadrupolar series, the C2 expansion or ethynylogation effect is more particularly considered for 9H-fluoren-2-yl, tris(O-n-alkyl)pyrogallyl, indol-3-yl, 4-anilinyl, and tetraphenyl-carbo-phenyl substituents on the following respective properties: two-photon absorption, chemical stability, columnar mesogenicity, on-surface photoinduced charge separation vs single-molecule conductance, and reduction potential. Topical results and prospects of application are discussed on the basis of crystallographic, spectroscopic, and electrochemical analyses vs DFT-calculated nuclear and electronic structures. For the sake of the discussion consistency, complementary experimental and computational results are disclosed in the dianilinyl series. Overall, it is shown that combined advances in strategy, protocols, and substrate scope of acetylenic synthesis remain crucial for the development of yet poorly explored but promising types of molecular materials.1 Introduction2 Hexaalkynyl-carbo-benzene3 ortho-Dialkynyl-carbo-benzene4 para-Dialkynyl-carbo-benzenes4.1 Bistrimethylsilylethynyl-carbo-benzene4.2 Bisfluorenylethynyl-carbo-benzene4.3 Bistrialkoxyarylethynyl-carbo-benzenes4.4 Bisindolylethynyl-carbo-benzene4.5 Bisanilinylethynyl-carbo-benzene5 Carbo-oligo(phenyleneethynylene)s6 Conclusions
Keywords: alkyne; C2 tether; carbo-benzene; carbo-mer; π-conjugation